Implicações de fatores ambientais na capacidade de trabalho dos enfermeiros em Unidades de Terapia Intensiva (UTI). - Aversari, Rawlla Eriam Oliveira Costa (2010)
The Intensive Care Unit (ICU) is considered the most aggressive sector of Unity Hospital where demand is intense, and the worker must be prepared for at any time, assist patients with significant hemodynamic changes, which require specific knowledge and skills, to make the right decisions and timely. We know also that the environment of an ICU is considered burdensome and stressful, and when coupled with environmental and organizational factors can interfere with the work ability of nurses. This study applied the questionnaires and equipment used to measure the variables, supported by national and international standards to analyze the relationship of the independent noise,temperature and lighting, and perceptual variables with respect to the thermophysical comfort, ie, those that are inherent subjective personal perception related to thermal comfort, which can be understood as psycho-physiological feelings of people towards the environment and other organizational and personal variables such as length of service, age and shift work, and how they interfere with the capacity The Work of the nurses. From reading the descriptive analysis and modeling ordinal multinomial regression was observed among several analysis that men are 78.41 times more likely to get index of the Work Ability (ICT) rather than women, in relation to schooling , 40.60% are college level and 59.40% technical or incomplete high school, where nurses with higher education are 18.72 times more likely to have the ICT in a range higher than a technical and / or nursing assistant; the each year working as a nurse, 24.61% increase in the chances of your falling-level ICT, nurses working the night shift have 92% more likely to have ICT at a lower level than those who work during the day . It was found that stability, upgrading formational, workload mild conditions and thermophysical controllable in the ICU may increase the work ability of nurses.